Genome-wide identification of the C2H2 zinc finger gene family in Populus euphratica and the functional analysis of PeZFP38 under salt stress - Zhao, Yazhi; He, Zhengquan; Fan, Lijiao; Liu, Huan; Chen, Huiling; Yang, Yuying; Fan, Na; Han, Xiaojiao; Lu, Zhuchou; Zhuo, Renying (Frontiers in Plant Science, 2026)
The C2H2 zinc finger protein (C2H2-ZFP) is a large transcription factor (TF) in plants, widely distributed across plants and playing crucial roles in growth, development, and responses to abiotic stress. However, most studies on the C2H2-ZFP gene family have mainly focused on model plants. In this study, we systematically identified the C2H2-ZFP gene family members in Populus euphratica, a tree species with high tolerance to salt and alkali stress, by analyzing gene localizations, conserved motifs, gene structures, and phylogenetic relationships. A total of 67 members of the P. euphratica C2H2-ZFP gene family were identified and were divided into five subfamilies. Promoter analysis revealed numerous cis-acting elements related to development, hormones, and abiotic stress. Both tandem and segmental duplications were identified as the main driving forces behind the expansion of the PeZFP gene family. Expression profiling showed that most PeZFPs exhibit tissue-specific expression patterns and respond to salt stress. Among them, PeZFP38 was strongly induced by salt stress in roots, stems, and leaves, with expression levels increased by 4.3–10.2-fold, 6–10.4-fold, and 28–63.7-fold, respectively. Subcellular localization demonstrated that PeZFP38 is a nuclear protein. Functional assays showed that transient overexpression of PeZFP38 in poplar leaves enhanced salt tolerance, and stable overexpression of PeZFP38 in Arabidopsis thaliana increased biomass (~68% fresh weight), enhanced antioxidant enzyme activities (e.g., SOD activity reached 1.7-fold that of WT), and reduced oxidative damage (~30% MDA decrease). These results suggest that PeZFP38 may play a role in enhancing salt tolerance by integrating ABA signaling with ROS scavenging systems. Collectively, this study systematically deciphers the evolutionary relationships and expression patterns of the C2H2-ZFP family in P. euphratica. For the first time, it functionally identifies the positive regulatory role of PeZFP38 in salt stress response. These findings provide novel genetic resources and a theoretical basis for understanding stress resistance mechanisms and genetic improvement in forest trees.